Bibliometric Analysis of Environmental Strategy Research - Loso Judijanto (West Science Social and Humanities Studies, 2026)
This study aims to examine the intellectual structure, development, and emerging trends in environmental strategy research using a bibliometric approach. Data were collected from the Scopus database, covering publications within a defined time span, and analyzed using VOSviewer to visualize relationships among key topics, authors, and research clusters. The findings indicate that environmental strategy research is predominantly centered on sustainable development, which serves as the core theme linking various subdomains such as environmental impact, climate change, and economic and social outcomes. The results also reveal a strong interdisciplinary integration with environmental science, particularly in areas related to remediation, toxicity, and risk assessment, as well as an expanding connection with health-related research. In addition, emerging themes such as artificial intelligence, machine learning, and data-driven decision-making suggest a shift toward more technologically enabled environmental strategies. Overall, the study highlights the evolution of environmental strategy from a compliance-based perspective to a dynamic and capability-oriented field that integrates sustainability, science, and digital innovation. These findings provide valuable insights for researchers and practitioners in identifying research gaps and shaping future directions in environmental strategy.